PENGARUH LINGKUNGAN MASYARAKAT TERHADAP MOTIVASI BELAJAR SISWA KELAS 5 SD Negeri 091320 Raya Tongah - Alexander Samosir (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Environmental conditions (family environment, school environment, and community environment) Raya Togah, Simalungun Regency greatly influences the learning motivation of grade 5 students at SD Negeri 091320 Raya Tongah, Simalungun Regency. , providing motivation in community learning, teachers in The problems faced by SD Negeri 091320 Raya Tongah Simalungun Regency in increasing student learning motivation are: not all teachers are professional in carrying out their duties, lack of active role of parents of students, limited supporting facilities and infrastructure..